Os sistemas de informação de uma organização e a sua segurança - Fernandes, Carlos Miguel Rocha (2022)
The development of the following internship report arises from the completion of the curricular unit of internship, with a duration of four months (600 hours), in the Statutory Auditors Firm Vieira, Bastos & Associado, Lda, in order to finalize the Master in Auditing of the Instituto Superior de Contabilidade e Administração do Porto. This report consists of a broad study and learning process, which includes the literature review that focuses on information, its security and financial auditing. With the culmination of this study, a practical case was carried out as a result of the curricular internship, where all the work developed along the same is described, in the scope of an audit of accounts review. With all this practical work developed it was possible to understand that an audit of audited accounts is not only to meet the standards implemented by regulatory bodies in this environment, nor by technological developments, but that much of the work developed and the decisions taken come from the judgment of the auditor himself who develops this work, having a leading role in this profession and development of this audit work.